(untitled) - Kruse, Robert L. (Upper Saddle River, N.J., 1997)
Progressing from the concrete to the abstract — and using numerous, substantial case studies and sample programs — this book explores structured problem solving, data abstraction, software engineering principles, and the comparative analysis of algorithms as fundamental tools of program design. Emphasizes principles of top-down refinement, program design, review, and testing. Uses the C programming language throughout. Offers Internet access to the source code for all the programs and program extracts printed in the book.
Keywords: C (Computer program language),Ngôn ngữ lập trình C